Circular bioeconomy business models - energy recovery from agricultural waste: cases from Kenya and Burkina Faso - Gebrezgabher, Solomie A.; Taron, Avinandan; Odero, J.; Sanfo, S.; Ouédraogo, Ramata; Salack, S.; Diarra, K.; Ouédraogo, S.; Ojungobi, K. (CGIAR Initiative on Nature-Positive Solutions, 2022)
Agricultural waste can be widely adopted to manufacture biogas or biofuel, which is obtained from biomass or agricultural wastes like molasses, bagasse slurries manure etc. Agricultural waste is mostly burned or left decomposing on the fields, where it has potential for polluting the environment and release greenhouse gases. Recovering energy helps to (i) reduce greenhouse emissions by reducing environmental pollution from unwanted biomasses otherwise being burnt in the field; (ii) improve energy efficiency in heating systems from renewable energy sources; (iii) introduce renewable energy by substituting carbon neutral biomass for hydro-carbons (coal, heavy oil and gas); and (iv) Recycle ash residues or slurry as a fertilizer. The present report covers four case studies from Kenya and Burkina Faso related to recovering energy from agrowaste. Biogas International Limited (BIL) is a public private venture in Kenya involved in collection of market waste and recovering biogas, compost, liquid bio fertilizer. The Dunga Beach biogas plant in Kenya turns the invasive water hyacinth (Eichhornia crassipes) on the shores of Lake Victoria to biogas energy, an alternative to charcoal burning for fish vendors at the beach. Keveye Girls is a boarding high school located in Vihiga County. Through consultations and interventions by the Department of Agriculture and Livestock at Vihiga County, Keveye Girls now converts cow dung into biogas, which is then used to power the school’s science laboratories and kitchen as an alternative to LPG gas and wood energy. Similar case studies exist in Burkina Faso. FasoBiogaz, an SME was founded by two Dutch entrepreneurs and supported by the Dutch government and is fully operated by a local team. FasoBiogaz operates the first industrial biogas plant connected to the SONABEL power grid and provides innovative resource recovery solutions producing 550 KW of power.